2021
DOI: 10.1177/01708406211053227
|View full text |Cite
|
Sign up to set email alerts
|

When Relationships Get in the Way: The emergence and persistence of care routines

Abstract: Past research has shown that routines can be a vehicle for both stability and change in organizations. It is unclear however how this relationship alters and solidifies over time. In this paper, the changing behaviours of three newly-formed teams within a domiciliary care organization are tracked over a period of two years. It was seen that self-reinforcing processes shaped the emergence and persistence of action patterns within these groups. The first process achieved coordination benefits which drove the eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
(135 reference statements)
1
6
0
Order By: Relevance
“…Synthesizing extant research, Dobusch and Schüßler (2013) propose four types of self-reinforcing mechanisms: coordination effects, complementarity effects, investment and learning effects, and expectation effects, in line with recent empirical investigations of path dependence (see e.g. Breslin, 2022;Stache & Sydow, 2022). The data revealed that expectation effects especially, as well as learning and investment effects, were dominant in these family firm cases.…”
Section: Data Coding and Analysissupporting
confidence: 68%
See 2 more Smart Citations
“…Synthesizing extant research, Dobusch and Schüßler (2013) propose four types of self-reinforcing mechanisms: coordination effects, complementarity effects, investment and learning effects, and expectation effects, in line with recent empirical investigations of path dependence (see e.g. Breslin, 2022;Stache & Sydow, 2022). The data revealed that expectation effects especially, as well as learning and investment effects, were dominant in these family firm cases.…”
Section: Data Coding and Analysissupporting
confidence: 68%
“…As elaborated in the model section, path breakage was often triggered by external shocks coinciding with family-internal changes. While these two systems are not in place in nonfamily firms, the findings still highlight the importance that social relationships might also have in other types of firm –so far given little thought in the context of path dependence (Breslin, 2022).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Routine dynamics rejects the idea that successful implementation primarily relies on how well routines have been designed, or that it is mainly a matter of convincing routine participants of the projected benefits with the intention of avoiding resistance (Breslin, 2022;Wegener & Glaser, 2021). As Pentland and Feldman (2008, p. 245) found in their study of a failed software implementation process, designing routines while hoping for actions is often grounded in a "naïve top-downism [that] assumes that good artifacts will result in good performance."…”
Section: A Routine Dynamics Perspective: Unpacking Synergy Realizationmentioning
confidence: 99%
“…Routine dynamics rejects the idea that successful implementation primarily relies on how well routines have been designed, or that it is mainly a matter of convincing routine participants of the projected benefits with the intention of avoiding resistance (Breslin, 2022; Wegener & Glaser, 2021). As Pentland and Feldman (2008, p. 245) found in their study of a failed software implementation process, designing routines while hoping for actions is often grounded in a “naïve top-downism [that] assumes that good artifacts will result in good performance.” In their conclusions, they urge organizational actors tasked with the design of routines not to treat them “like a piece of furniture” (Pentland & Feldman, 2008, p. 248) that can be moved and put up wherever needed, but instead to consider them as endogenously dynamic (Feldman & Pentland, 2003), potentially ambiguous (Yamauchi & Hiramoto, 2016), and part of a larger network of actors and actions (see Rosa et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%